Soundscapes in English and Spanish: a corpus investigation of verb constructions - Paradis, Carita; Caballero, Rosario (Lund University, 2020)
This corpus study explores how SOUND events are communicated in English and Spanish. The aims are to (i) contribute production data for a better understanding of the couplings of meanings and their realizations in the realm of SOUND, (ii) account for typological differences between the two languages, and (iii) further the theoretical discussion of how SOUND is conceptualized through the window of language. We found that while there are significant differences between the languages with respect to how SOUND events are communicated, they are similar with respect to what domains the sound descriptions are instantiated in, namely PERCEPTION (including the more specific domain of sound), MOTION, MANIPULATION, EMOTION-REACTION, CONSUMPTION and COGNITION. One striking difference has to do with the conflation of SOUND FOR ACTION, e.g., creak, squeak, and SOUND FOR MOTION, e.g., slam, crash. This finding supports the received view of English as a language that may lexicalize MANNER in those kinds of verbs, while Spanish expresses MANNER through qualifiers outside the verb. Moreover, both languages employ three different perspectives on the soundscapes: Producer-, Experiencer- and Phenomenon-based. While English favours the Producer perspective, Spanish features an even distribution between Producer and Experiencer. Phenomenon-based descriptions are relatively few in both languages.

Acorpus of 951,903 words (415,594 in English and 536,309 in Spanish) with narratives from three different popular genres in English and Spanish, namely fantasy (Throne of glass by Sarah Maas and El último Catón by MThrone of glass by Sarah Maas and El último Catón by Matilde Asensi), romance (Beyond sunrise by Candice Proctor and El tiempo entre costuras by María Dueñas) and thriller (The silkworm by Robert Galbraith and El verano de los juguetes rotos by Toni Hill).

Denna korpusstudie undersöker hur LJUD-händelser kommuniceras i engelska och spanska. Vi vill med denna data bidra med produktionsdata för att bättre förstå kopplingen mellan betydelser och hur de uttrycks inom domänen LJUD. Vi vill också se på vilket sätt engelskan och spanskan liknar varandra och hur de skiljer sig.

En korpus baserad på 951,903 ord (415,594 och 536,309 på spanska. Texterna är narrativer från tre olika populärgenrer: fantasy, romantik och thrillers
Soundscapes in English and Spanish: a corpus investigation of verb constructions
Keywords: cognitive semantics; kognitiv semantik; sensory perceptions; sensorisk perception; hearing; hörsel; concept driven; konceptdriven; lexicalization; lexikalisering; motion; rörelse; manipulation; manipulation; synaesthesia; synestesi; embodiment; förkroppsligande; Humanities and the Arts; Humaniora och konst; Languages and Literature; Språk och litteratur